Temperature-dependent potential for the molecular dynamics of the superionic conductor β-PbF2. Issue 3 (March 2022) - López, J.D.; Diosa, J.E.; García, G.; Mosquera, E.; Correa, H.
Abstract: Molecular dynamic (MD) calculations were performed to investigate the thermodynamic and structural properties of lead fluoride (PbF2 ) by using a proposed inter-ionic temperature-dependent potential. This potential allows calculating with high precision the linear thermal expansivity and the lattice parameter as a temperature function. In addition, the potential can be represented as a sum of two contributions, a temperature-independent potential added to another temperature-dependent potential, considered last as a correction justified by the one-dimensional Newtonian quantum equation. Two fitting regions were considered, the first region from 300 to 700 K and the other one from 700 to 900 K. These regions arise naturally due to the smooth and continuous transition that PbF2 undergoes until it reaches the superionic state and, allows us to model with high precision the anomaly in the dependence of the lattice parameter with the temperature of this material, a feature that until now under the molecular dynamic method has not been studied. These results are all in good agreement with the experimental measurements. Abstract : Superionic conductor; Lead fluoride (PbF2 ); Molecular dynamics (MD).